Narrative Structure of `The Minds of Billy Milligan` Novel and `Split` Film: A Comparative Study - M. Keanu Adepati; Samanik Samanik (Universitas Muhammadiyah Semarang, 2018)
This paper discusses about the narrative structure adaptation of Split Movie (2017) from The Minds of Billy Milligan novel by Daniel Keyes. Mainly, this research is to reveal how the Split movie by M. Night Shyamalan adapts the narrative structure of The Minds of Billy Milligan novel by Daniel Keyes. In order to achieve the research objective, the writer used a qualitative method since the writer would like to describe the detail of the adaptation. In this research the theory that used is the narrative structure theory by Tzvetan Todorov in the concepts of equilibrium, disruption, recognition, restored order, equilibrium and using a structuralism approach in characters and the setting. The data sources of this analysis are from both The Minds of Billy Milligan novel by Daniel Keyes and Split movie by M. Night Shyamalan. After getting the data, the writer classified the data based on the Todorov’s theory. Subsequently, the analysis describes the comparison of both works structurally. Eventually, this study shows the narrative structure of The Minds of Billy Milligan novel which are adapted in Split movie.